The potential science and engineering value of samples delivered to Earth by Mars sample return. (5th March 2019) - ,; Beaty, D. W.; Grady, M. M.; M Sween, H. Y.; Sefton‐Nash, E.; Carrier, B. L.; Altieri, F.; Amelin, Y.; Ammannito, E.; Anand, M.; Benning, L. G.; Bishop, J. L.; et al.
Abstract: Executive summary provided in lieu of abstract.